Energy dissipation and performance assessment of double damped outriggers in tall buildings under strong earthquakes. (3rd October 2018) - Morales‐Beltran, Mauricio; Turan, Gürsoy; Dursun, Onur; Nijsse, Rob
Summary: The use of a single set of outriggers equipped with oil viscous dampers increases the damping ratio of tall buildings in about 6–10%, depending on the loading conditions. However, could this ratio be further increased by the addition of another set of outriggers? Should this additional set include dampers too? To answer these questions, several double damped outrigger configurations for tall buildings are investigated and compared with an optimally designed single damped outrigger, located at elevation 0.7 of the total building's height (h). Using free vibration, double outrigger configurations increasing damping up to a ratio equal to the single‐based optimal are identified. Next, selected configurations are subjected to several levels of eight ground motions to compare their capability for avoiding damage under critical excitations. Last, a simplified economic analysis highlights the advantages of each optimal configuration in terms of cost savings. The results show that, within the boundaries of this study, combining a damped outrigger at 0.5h with a conventional outrigger at 0.7h is more effective in reducing hysteretic energy ratios and economically viable if compared with a single damped outrigger solution. Moreover, double damped outrigger configurations for tall buildings exhibit broader display of optimal combinations, which offer flexibility of design to the high‐rise architecture.